One-Dimensional Hydrodynamic Modeling of the Euphrates River and Prediction of Hydraulic Parameters - Nassrin Jassim Hussien Al-Mansori; Laith Shaker Ashoor Al-Zubaidi (Salehan Institute of Higher Education, 2020)
Forecasting techniques are essential in the planning, design, and management of water resource systems. The numerical model introduced in this study turns governing differential equations into systems of linear or non-linear equations in the flow field, thereby revealing solutions. This one-dimensional hydrodynamic model represents the varied unsteady flow found in natural channels based on the Saint-Venant Equations. The model consists of the equations for the conservation of mass and momentum, which are recognized as very powerful mathematical tools for studying an important class of water resource problems. These problems are characterized by time dependence of flow and cover a wide range of phenomena. The formulations, held up by the four-point implicit finite difference scheme, solve the nonlinear system of equations using the Newton-Raphson iteration method with a modified Gaussian elimination technique. The model is calibrated using data on the Euphrates River during the early spring flood in 2015. It is verified by its application to an ideal canal and to the reach selected at the Euphrates River; this application is also used to predict the effect of hydraulic parameters on the river’s flow characteristics. A comparison between model results and field data indicates the feasibility of our technique and the accuracy of results (R2 = 0.997), meaning that the model is ready for future application whenever field observations are available.